Authors` response to the letter to the editor: "Effects of acoustic feedback training in elite-standard Para-Rowing" by Schaffert and Mattes (2015) - Schaffert, N.; Mattes, K. (Journal of Sports Sciences, 2015)
Our article in the Journal of Sports Sciences was designed to examine effects of auditory feedback on mean boat speed during on-water training of visually impaired athletes in elite-standard Para-Rowing. This aim is stated explicitly in the title, abstract, introduction and discussion section. The effects were analysed on the basis of a conservative approach to using inferential statistics by emphasising measures that communicate meaningful differences and effect sizes to help interpret the data`s practical importance for sport competition. Biomechanical measurements have been combined with standardised questionnaires to assess the athletes` perceived experience during rowing with acoustic feedback. An application for high-performance rowing has already been used to successfully investigate the effects of acoustic feedback on the time structure of the rowing cycle during the recovery phase. In this response, we provide our comments to the concerns presented in the `Letter to the Editor` along with a brief description of the issues that relate to research in high-performance sport.